Survey Report: Directors of PG Teaching & Learning on 'Research Integrity and Impact in an Open Scholarship Era' Module [(RIOSE] - Learnovate (Trinity College Dublin, The University of Dublin, 2020)
Report of a survey conducted in August 2020 by Learnovate of TCD Directors of Postgraduate Teaching & Learning on the online module 'Research Integrity and Impact in an Open Scholarship Era'. The module is a compulsory element for all incoming doctoral students on Trinity's Structured PhD programme. This is an output of a SATLE project, funded by the National Forum for the Enhancement of Teaching & Learning.
Keywords: Instructional design, analysis; Open Science training